2017
DOI: 10.1002/joa3.12015
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors and prevention of dabigatran‐related gastrointestinal bleeding in patients with atrial fibrillation

Abstract: IntroductionDabigatran, as compared with warfarin, was associated with lower rates of stroke and systemic embolism with similar rates of major hemorrhage. But it has a significantly higher risk of gastrointestinal bleeding (GIB). There are limited data on how to prevent GIB from dabigatran and what are the risk factors.MethodsWe performed a retrospective cohort study of patients with atrial fibrillation who have ever taken dabigatran for thromboprophylaxis from October 2010 to February 2013.ResultsA total of 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 30 publications
0
16
0
Order By: Relevance
“…In the present study, bleedings appeared in 7.34% NOAC-treated patients. Phase III randomized trials comparing NOACs with warfarin and real-world studies [ 40 , 41 ] estimated the bleeding risk at 1 to 3% per year, and discontinuation of NOACs was less prevalent than with VKA [ 41 ]. As well, both individual studies and meta-analyses have shown that NOACs are associated with a lower incidence of fatal bleedings, lower in-hospital mortality, and a better evolution of patients suffering from bleedings, even intracranial ones [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the present study, bleedings appeared in 7.34% NOAC-treated patients. Phase III randomized trials comparing NOACs with warfarin and real-world studies [ 40 , 41 ] estimated the bleeding risk at 1 to 3% per year, and discontinuation of NOACs was less prevalent than with VKA [ 41 ]. As well, both individual studies and meta-analyses have shown that NOACs are associated with a lower incidence of fatal bleedings, lower in-hospital mortality, and a better evolution of patients suffering from bleedings, even intracranial ones [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…During the follow-up period, we did not register major bleedings, only CRNMB and minor bleeding episodes, easily managed by gastroenterologists and treating cardiologists. Generally, non-major bleedings were more common than the major ones in NOACs randomized trials [ 43 ] and real-world studies [ 40 , 41 ]. As shown before, also in our study, in the vast majority, predominated lower GIB [ 44 ] possible by incomplete absorption of the active substance in the upper tract and increased NOACs availability in the lower tract [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, we found that there was no significant differences in PPI between the two groups and had no protective effect on the incidence of GIB. Similarly, previous studies had reported that PPI could not decrease the incidence of GIB in patients after anticoagulant therapy with dabigatran [15]. It was noteworthy that a study that 46,301 patients with dual antiplatelet therapy after myocardial infarction were recruited, reported PPI could reduce the risk of GIB, However, long-term outcomes needed to be further observed [16].…”
Section: Discussionmentioning
confidence: 93%
“…As a rule, monitoring the effectiveness of the treatment carried out is not sufficient, especially when using the so-called New Oral Anticoagulants (NOAC), for which the necessary laboratory tests have not been developed yet. However, overdose and uncontrolled intake of anticoagulants and antiplatelet agents can cause serious hemorrhagic complications [12,13]. On the other hand, insufficiently effective antiplatelet therapy leads to complications of different kinds, associated with the risk of increased thrombosis.…”
Section: Introductionmentioning
confidence: 99%